Knowledge of sex stereotypes and internality - Félix Neto (1995)
204 Portuguese adolescents responded to the Portuguese version of the Sexual Stereotypes Measure II and to the Portuguese version of the Intellectual Achievement Responsibility Questionnaire. Positive correlations were found between male sex stereotype and internal attribution of responsibility for successful outcomes and female sex stereotype and internal attribution of responsibility for failing outcomes.